INVESTMENT FUNDS INDUSTRY IN ROMANIA - Adela Ionescu (Global Economic Observer)
Capital market offers those who study it and those who use it as traders or as investors, a feature similar to a paradox. Her specific routine operations are regulated to the level of detail bylaws, instructions, procedures or measures layouts while decisions on investments in securities and portfolio restructuring are taken under perpetual uncertainty. This has a twofold explanation, an objective one and a subjective one.Future prices, as well as successive conditions of stock exchange not necessarily flow from the past, thus one cannot predict their level and over them is hanging the conviction that any selected alternative action is probably the best without having any certainty that that is really correct and rational in an absolute mode.Even if the evaluation of factors influencing prices is a questionable one, there is the likelihood of good choices when doing a basic operation-selling or buying. Factors identified, evaluated and ranked may change in the next period their force of action or even the market structure so that exchange activity is at least difficult to determine.In this category is included the mutual fund industry, whose evolution in Romania was not without risk and has had a tortuous circuit thanks to immature capital markets and market actors but especially due to the permissive legislation during the start phase. A certain progress was recorded in the last 10 years,although the financial crisis made its mark on the capital market and revealed the negative impact of systemic risks.